Reduced resistance at molecular-crystal electrolyte and LiCoO2 interfaces for high-performance solid-state lithium batteries - Yuki Watanabe; Shigeru Kobayashi; Zheng Ruijie; Deng Jun; Kenjiro Tanaka; Kazunori Nishio; Ryo Nakayama; Ryota Shimizu; Makoto Moriya; Taro Hitosugi (APL Materials)
Molecular crystal electrolytes are promising solid electrolytes owing to their ionic conductivity and mechanical flexibility. However, solid-state batteries using these electrolytes suffer from the large resistance at the interfaces with positive electrodes. Herein, we fabricate a battery using Li{N(SO2F)2}(NCCH2CH2CN)2, referred to as Li(FSA)(SN)2, a molecular-crystal electrolyte, and demonstrate the stable thin-film battery cycling. The novel fabrication method forms electrochemically stable interfaces, allowing the thin-film batteries to cycle at a current density of up to 500 μA cm−2 in the voltage range of 3.00–4.05 V vs Li/Li+. This current density is 500 times higher than that reported previously. Notably, the Li(FSA)(SN)2–LiCoO2 interface resistance (24 Ω cm2) is comparable to that of the interface of liquid-electrolyte and LiCoO2 in Li-ion batteries. Furthermore, inserting an amorphous Li3PO4 layer into the Li(FSA)(SN)2–LiCoO2 interface enables stable cycling up to 4.30 V vs Li/Li+, suppressing the decomposition of electrolytes. These quantitative investigations and interfacial controls pave the way for the practical applications of molecular-crystal electrolytes to solid-state batteries.